A new approach to estimating the occupation time of the railway infrastructure - Gašparík, Jozef; Zitrický, Vladislav (Transport, 2010)
The paper describes UIC methodology and a technique used by Slovakian infrastructure managers for estimating railway capacity and proposes a new approach to evaluating the capacity consumption of a track line (occupation time) based on the graphic approach. The new methodology concerns for the assessment of infrastructure occupation time and is a conceptual framework developed by the authors for an easier evaluation of occupation time in the train traffic diagram. First published online: 10 Feb 2011